Perspective of Indonesian Pediatricians on the Role of PrebioticSupplemented Formula towards Immunity, Growth and Development in Preterm Infants: A Preliminary Data - Nova Lidia Sitorus; Charisma Dilantika; Ray Wagiu Basrowi (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2021)
ABSTRACT Background: Immature immune system in preterm infants is associated with gut dysbiosis and poses significant health risks to their growth and development. Current guidelines for managing preterm infants focuses solely on macro- and micronutrients, whereas preterm infants’ gastrointestinal system requires optimalization to support nutrient absorption. Studies on the positive impacts of prebiotics as supplements have been conducted, but has not been implemented in Indonesia. Indonesian pediatricians’ perspective on these findings needs to be assessed. Objectives: To describe the perspectives of Indonesian pediatricians on the role of gut microbiota balance in supporting immunity, growth, and development of preterm infants, and the role of breastmilk and prebiotic-supplemented formula in optimizing gut microbiota balance. Methods: A cross-sectional study was conducted on 114 Indonesian pediatricians using a previously-validated and previously-used questionnaire on the role of gut microbiota balance on preterm infants, as well as the role of breastmilk and prebiotic-supplemented formula in optimizing gut microbiota balance. Results: Most respondents agreed that gut microbiota balance supports immunity, growth, and development of preterm infants. Respondents also agreed that breastmilk contains nutrients that support gut microbiota balance and when breastmilk becomes unavailable, prebiotic-supplemented formula can be given as substitute. Conclusions: Indonesian pediatricians considered gut microbiota balance to be important for immunity, growth, and development of preterm infants, and breastmilk to be the most ideal source of nutrition for preterm infants in optimizing gut microbiota balance. When breastmilk is unavailable, prebiotic-supplemented formula can be considered as an alternative.